The Role of Construction BUMN Subsidiaries in Indonesia on the Performance of Parent Companies: in a Perspective and Concept - Iman Setya, Bobby; Firdiansyah Suryawan, Ryan; Sopyan, Ahmad (International Journal of Advanced Multidisciplinary, 2024)
This article will analyze how the formation and operation of subsidiaries affect the operational, financial, and strategic performance of construction SOE holding companies in Indonesia. This article uses a qualitative method with a literature review and a perspective used in by the researcher according to the available data sources to support this article. Analysis of findings and existing data from construction companies in Indonesia. The structure of the parent company and subsidiaries allows for flexible and integrated business management, reduces internal conflicts, and improves efficiency. Subsidiaries help the parent company expand markets, manage risks, and create synergies. The application of transaction cost theory shows that establishing a subsidiary can reduce transaction costs and improve operational control. Portfolio management and synergies between subsidiaries are also important to improve efficiency and competitiveness. Corporate diversification and good oversight mechanisms ensure alignment between the goals of the subsidiary and the parent company's strategy.